Alkene Metalates as Hydrogenation Catalysts. Issue 13 (6th February 2017) - Büschelberger, Philipp; Gärtner, Dominik; Reyes‐Rodriguez, Efrain; Kreyenschmidt, Friedrich; Koszinowski, Konrad; Jacobi von Wangelin, Axel; Wolf, Robert
Abstract: First‐row transition‐metal complexes hold great potential as catalysts for hydrogenations and related reductive reactions. Homo‐ and heteroleptic arene/alkene metalates(1−) (M=Co, Fe) are a structurally distinct catalyst class with good activities in hydrogenations of alkenes and alkynes. The first syntheses of the heteroleptic cobaltates [K([18]crown‐6)][Co(η 4 ‐cod)(η 2 ‐styrene)2 ] (5 ) and [K([18]crown‐6)][Co(η 4 ‐dct)(η 4 ‐cod)] (6 ), and the homoleptic complex [K(thf)2 ][Co(η 4 ‐dct)2 ] (7 ; dct=dibenzo[ a, e ]cyclooctatetraene, cod=1, 5‐cyclooctadiene), are reported. For comparison, two cyclopentadienylferrates(1−) were synthesized according to literature procedures. The isolated and fully characterized monoanionic complexes were competent precatalysts in alkene hydrogenations under mild conditions (2 bar H2, r.t., THF). Mechanistic studies by NMR spectroscopy, ESI mass spectrometry, and poisoning experiments documented the operation of a homogeneous mechanism, which was initiated by facile redox‐neutral π‐ligand exchange with the substrates followed by H2 activation. The substrate scope of the investigated precatalysts was also extended to polar substrates (ketones and imines). Abstract : Homo‐ or heterogeneous catalysis? A series of nine alkene and arene metalates (M=Fe, Co) were prepared and studied as precatalysts in hydrogenation reactions (see scheme). Excellent catalytic activities in olefin hydrogenations were observed. The catalyst activation mechanism by redox‐neutral π‐ligand exchange was monitored by NMR spectroscopy and ESI‐MS experiments.